The impact of cultural tourism experience on electronic word-of-mouth (e-WOM) and destination image - Ardiwansyah Nanggong; Ali Mohammad (Diponegoro International Journal of Business, 2020)
Tourism experience is considered highly essential in tourism studies but less attention to research has focused on cultural tourism experiences whereas has its idiosyncratic compared to other types of tourism. This study investigated the interrelationship among cultural tourism experiences, electronic word of mouth, and destination image. Empirical analysis based on data collected through online questionnaires from 134 tourists have been visited the religious-cultural tourism village Bongo in Gorontalo. PLS-SEM conducted to data analysis which showed that cultural tourism experience positively impacts on destination image and electronic word of mouth, also electronic word of mouth influence destination image. This research contributes to the body of knowledge on the role of tourism experience and its impact on future tourist behavior in the cultural tourism context. The theoretical and managerial implications of these findings are beneficial in designing strategies to leverage destination attractiveness